Isolation, Identification, and Selection of Bacteria With Proof-of-Concept for Bioaugmentation of Whitewater From Wood-Free Paper Mills - Verdel, Nada; Rijavec, Tomaž; Rybkin, Iaroslav; Erzin, Anja; Velišček, Žiga; Pintar, Albin; Lapanje, Aleš (Frontiers in Microbiology, 2021)
In the wood-free paper industry, whitewater is usually a mixture of additives for paper production. We are currently lacking an efficient, cost-effective purification technology for their removal. In closed whitewater cycles the additives accumulate, causing adverse production problems, such as the formation of slime and pitch. The aim of our study was to find an effective bio-based strategy for whitewater treatment using a selection of indigenous bacterial isolates. We first obtained a large collection of bacterial isolates and then tested them individually by simple plate and spectrophotometric methods for their ability to degrade the papermaking additives, i.e., carbohydrates, resin acids, alkyl ketene dimers, polyvinyl alcohol, latex, and azo and fluorescent dyes. We examined correlation between carbon source use, genera, and inoculum source of isolates using two multivariate methods: principal component analysis and FreeViz projection. Of the 318 bacterial isolates, we selected a consortium of four strains (Xanthomonadales bacterium sp. CST37-CF, Sphingomonas sp. BLA14-CF, Cellulosimicrobium sp. AKD4-BF and Aeromonas sp. RES19-BTP) that degrade the entire spectrum of tested additives by means of dissolved organic carbon measurements. A proof-of-concept study on a pilot scale was then performed by immobilizing the artificial consortium of the four strains and inserting them into a 33-litre, tubular flow-through reactor with a retention time of <15 h. The consortium caused an 88% reduction in the COD of the whitewater, even after 21 days.